2022
DOI: 10.1002/fes3.432
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of Striga resistant maize varieties and fertilizer use in Ghana: A panel analysis

Abstract: This study analyzes the impact of a component of climate-smart agriculture (CSA) technology-Striga-resistant maize (SRM) varieties and mineral fertilizer-on maize yield and food security using two rounds of panel data in Ghana. The study employs a multinomial endogenous switching regression model and finds that joint adoption of SRM varieties and mineral fertilizer increased maize yield by 872 kg/ha, food consumption scores by 17, and consumption per adult equivalent unit by 38 kg/ha. The positive impact of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Feder [17] first attempted to evaluate the interaction of various agricultural technologies adopted by farmers. Recently, studies on the adoption of multiple agricultural technologies (MATs) in the joint estimation framework have begun to increase [1,18,19]. Some scholars have considered conservation agriculture (CA), climate-smart agriculture (CSA), integrated soil fertility management (ISFM), sustainable agricultural practices (SAPs), and sustainable intensification practices (SIPs) as research objects to analyze the factors of various technologies adopted by farmers [4,9,[20][21][22].…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…Feder [17] first attempted to evaluate the interaction of various agricultural technologies adopted by farmers. Recently, studies on the adoption of multiple agricultural technologies (MATs) in the joint estimation framework have begun to increase [1,18,19]. Some scholars have considered conservation agriculture (CA), climate-smart agriculture (CSA), integrated soil fertility management (ISFM), sustainable agricultural practices (SAPs), and sustainable intensification practices (SIPs) as research objects to analyze the factors of various technologies adopted by farmers [4,9,[20][21][22].…”
Section: Section 1: Introductionmentioning
confidence: 99%
“…However, it also increased family labor demand, especially for women. Meanwhile, using a similar approach, Martey et al (2023) found that the joint use of Striga-resistant maize and fertilizers had significant positive effects on yields and food consumption. Likewise, using a similar approach, Kassie et al (2015) found evidence of improved food security and reduced downside risk when Malawian farmers simultaneously adopted maize varieties and chemical inputs.…”
mentioning
confidence: 99%